A multilevel framework to reconstruct anatomical 3D models of the hepatic vasculature in rat livers. Issue 3 (20th December 2016) - Peeters, Geert; Debbaut, Charlotte; Laleman, Wim; Monbaliu, Diethard; Vander Elst, Ingrid; Detrez, Jan R.; Vandecasteele, Tim; De Schryver, Thomas; Van Hoorebeke, Luc; Favere, Kasper; Verbeke, Jonas; Segers, Patrick; et al.
Abstract: The intricate (micro)vascular architecture of the liver has not yet been fully unravelled. Although current models are often idealized simplifications of the complex anatomical reality, correct morphological information is instrumental for scientific and clinical purposes. Previously, both vascular corrosion casting (VCC) and immunohistochemistry (IHC) have been separately used to study the hepatic vasculature. Nevertheless, these techniques still face a number of challenges such as dual casting in VCC and limited imaging depths for IHC. We have optimized both techniques and combined their complementary strengths to develop a framework for multilevel reconstruction of the hepatic circulation in the rat. The VCC and micro‐CT scanning protocol was improved by enabling dual casting, optimizing the contrast agent concentration, and adjusting the viscosity of the resin (PU4ii). IHC was improved with an optimized clearing technique (CUBIC) that extended the imaging depth for confocal microscopy more than five‐fold. Using in‐house developed software ( DeLiver ), the vascular network – in both VCC and IHC datasets – was automatically segmented and/or morphologically analysed. Our methodological framework allows 3D reconstruction and quantification of the hepatic circulation, ranging from the major blood vessels down to the intertwined and interconnected sinusoids. We believe that the presented framework will have value beyond studies of the liver, and will facilitate a better understanding of various parenchymal organs in general, in physiological and pathological circumstances.